Characterisation of PET nonwoven deposited with Ag/FC nanocomposite films. (2nd November 2018) - Xu, WenZheng; Yuan, XiaoHong; Wei, AnFang; Feng, Quan; Wei, QuFu
ABSTRACT: Silver/fluorocarbon (Ag/FC) nanocomposite films were successfully deposited on the polyester (PET) nonwoven using magnetron sputtering techniques with pure silver (Ag) and polytetrafluoroethylene (PTFE) targets. FT-IR, XPS, XRD and EDX were used to examine the compositions and structure of Ag and Ag/FC films. SEM and AFM were employed to observe the surface morphology. Hydrophobicity properties and electromagnetic shielding properties of the Ag- and Ag/FC-coated PET nonwoven were also investigated. The experimental results showed that the films deposited on PET nonwoven were even and dense. The Ag existed in the films was elemental silver which had high degree of crystallinity. In contrast, the FC film did not form crystalline structure containing five components, i.e. –CF3, –CF2 –, –CF–, –C–CF– and –C–C–, C–F groups clearly observed by the FT-IR spectrum. Compared with the original PET nonwoven, hydrophobicity properties and electromagnetic shielding properties of the PET nonwoven deposited with Ag/FC nanocomposite films were improved significantly.